The impact of costs and perceived quality on utilisation of primary health care in Tanzania : rural-urban comparison - Munga, Michael A (Health Economics Unit, 2018)
Health services utilisation, which is sometimes used as a proxy measure for equity is a complex subject to study. Identifying and explaining the important factors determining health care utilisation is a key to a better assessment of whether countries' health policies address the equity concerns of their populations in a comprehensive way. It is extensively documented that meeting the health needs of people especially those disadvantaged by such factors as geographical location, joblessness, low income, gender inequalities and lack of education among others, is an important strategy to preventing the increase in poverty and eventually reducing equity gaps. Realising this goal is not easy unless studies are done to establish policy and theoretical arguments related to why some sections of populations are more likely to use/or not to use available health care services than others. This cross-sectional study principally aims at assessing the impact of perceived quality and costs of health care on utilisation of PHC services in rural and urban areas of Tanzania. Using both quantitative and qualitative methods, it intends to explore whether there are differences between rural and urban users in terms of their perceptions of quality of health services and how these perceptions affect household decisions in utilising health services. It further examines the extent to which costs of health care are important determinant in health services utilisation and how rural and urban users are affected by this factor when it comes to deciding to use or not to use government health facilities. The study concludes that consumers of health care in rural Tanzania are highly responsive to health care costs than they are to quality concerns. As the two categories of rural and urban are affected differently by costs and their perceptions of quality when it comes to health care utilisation, it is possible that the observed utilisation trends can partly be attributed to these two factors. Furthermore, the study highlights that socio-economic variables such as gender, income, education, wealth and household size are important not only in determining user's decision making on the amount and appropriate time to seek care but also mitigates effectively on the extent to which costs and perception of quality of care affect rural and urban users of health care services. The study recommends that the government should strive to provide better "quality " information to its consumers. It further recommends that a critical evaluation of important quality aspects be done to see which mostly determine household decisions on utilisation of care among rural and urban users of care. The study has found that the kit system has had some problems, hence the study recommends that government devises mechanisms of ensuring that drugs are available at points of service. Acknowledging the existing geographical inequities, the need to incorporate the private sector in PHC provision and improve quality of health care, the study recommends for more resources to be devoted to research and venture on new opportunities provided by the ongoing reforms as a way of introduction, chapter one of the study report presents the country background information and how the health system is organised. The remainder of the report is organised as follows. In chapter two, the report presents the literature review whilst chapter three covers conceptual framework and methodology. This is followed by presentation of results and analysis in chapter four before putting forward a brief discussion of the findings in chapter five. In chapter six, conclusions and policy recommendations are presented.